(untitled) (Journal of the College of Basic Education, 2022)
Education for sustainable development is a demand, which I urged the United Nations to adopt, in order to interact the entire educational process with development challenges, national and global, and to harness education to prepare the necessary competencies for planning to mitigate the impact of these challenges or adapt to them. Since such education is a developmental necessity and an urgent need to secure the development goals of peoples, it is first for the foundations of university education to be based on its principles (education for sustainable development) or at least to include in the quality standards of universities foundations, concepts and determinants related to the essence of education for sustainable development, whether in The institutional structure of universities or the vocabulary of their performance, such as curricula, research or field practices.